Glabridin‐Gold(I) Complex as a Novel Immunomodulatory Agent Targeting TrxR and MAPK Pathways for Synergistic Enhancement of Antitumor Immunity - Zhaoran Wang (Advanced Science, 2025)
Abstract Metal‐based drugs have been utilized as immunomodulatory agents in combination with cancer immunotherapies to induce tumor immunogenicity. However, the immunosuppressive tumor microenvironment significantly hinders the efficacy of these immunomodulatory agents from promoting antitumor immune responses. Herein, a novel metal‐based immunomodulatory agent, 6d, is developed by integrating N‐heterocyclic carbene gold(I) [NHC‐Au(I)] with the natural product glabridin (GLA). Complex 6d aims to promote tumor immunogenicity while suppressing immunosuppression, by targeting thioredoxin reductase (TrxR) and the mitogen‐activated protein kinase (MAPK) pathways. Notably, 6d enhances dendritic cell (DC) maturation while reducing myeloid‐derived suppressor cells (MDSCs), M2‐type macrophages, and regulatory T cells (Tregs) in liver cancer. Moreover, 6d exhibits a synergistic effect of gold center and GLA, suppressing programmed cell death 1 ligand 1 (PD‐L1) expression in tumor cells while promoting granzyme B (GzmB) production in T cells. These findings suggest that dual inhibition of TrxR and MAPK may provide a synergistic strategy to stimulate antitumor immunity while mitigating the immunosuppressive tumor microenvironment. Overall, this study warrants further researches to determine therapeutic efficacy of 6d as an immunomodulatory agent in combination with cancer immunotherapies.